Peranan objek dramatik dalam perkembangan naratif. Projek filem tahun akhir : Siaran tergendala - Abraham Japheth Jarak, Bin Albert. (Universiti Malaysia Sarawak (UNIMAS), 2007)
The research is regarding to the role ofdramatic object in narative development. In this research, the reseacher focused on the role of the dramatic object that animate tha narative story and help the main character to overcome the conflict. This research also focused on how the object give rise to the conflict to the main character and give effict to the another characters. In this short video project bicycle as the dramatic object that give effect in the narative story.Siaran Tergendala is one part ofresearch for dramatic object role in narative development.